2005
DOI: 10.1381/0960892054621099
|View full text |Cite
|
Sign up to set email alerts
|

Adjustable Gastric Banding in an Ambulatory Surgery Center

Abstract: LAGB has become an appropriate outpatient procedure in select patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
44
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 8 publications
3
44
0
2
Order By: Relevance
“…The 2006 American Society of Anesthesiologists practice guidelines for perioperative management of patients with OSA were developed with the aim to help practitioners make rational decisions and provide optimal perioperative care to those patients (17). However, some practitioners do not consider appropriately treated as a contraindication for ambulatory LAGB (6,18). Such an approach is actually supported by this study that demonstrated similarities in non-ambulatory (39.1%) and ambulatory outcomes (37.4%) of patients with OSA (p=0.83).…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…The 2006 American Society of Anesthesiologists practice guidelines for perioperative management of patients with OSA were developed with the aim to help practitioners make rational decisions and provide optimal perioperative care to those patients (17). However, some practitioners do not consider appropriately treated as a contraindication for ambulatory LAGB (6,18). Such an approach is actually supported by this study that demonstrated similarities in non-ambulatory (39.1%) and ambulatory outcomes (37.4%) of patients with OSA (p=0.83).…”
Section: Discussionsupporting
confidence: 54%
“…Skilled surgeons require roughly 1 h of operative time for completion of LAGB (8,18). Reported conversion rates to an open procedure have ranged from 0% in private practice settings to 8% at academic institutions where residents are involved (6,7). A mean surgical time of 70 min with no conversions to an open procedure in the current study points towards a reliable surgical technique.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…23 Gastric banding procedures induce considerable weight loss in obese subjects. 24,25 Gastric bypass, the most frequent operation performed in USA, is more invasive and still more efficient, with satisfactory >60% EWL. 2,26 Biliopancreatic diversion of Scopinaro et al 27,28 is a mixed and complex operation that, in association with nutrient supplementation to avoid nutritional deficiency, has shown the most effectiveness in weight loss and permanent normalization of serum glucose, triglyceride, and cholesterol levels, with results maintained for >10 years follow-up.…”
Section: Discussionmentioning
confidence: 99%